The host transcriptome change involved in the inhibitory effect of exogenous interferon-γ on Getah virus replication - Li, Jialei; Gao, Xintao; Liu, Xingjian; Wu, Tong; Song, Haozhi; Gao, Weisong; Jia, Hong; Li, Yinü; Zhang, Zhifang (Frontiers in Microbiology, 2023)
Getah virus (GETV) has become a growing potential threat to the global livestock industry, and even to public health. However, little is known about the viral pathogenesis and immune escape mechanisms, consequently leading to the lack of effective control measures. In this study, the antiviral activity of exogenous interferons (IFNs) was assessed, the result showed that treatment with IFN-γ could obviously suppress GETV replication and the inhibiting effect lasted for at least 48 hours, while the exogenous IFN-α/ω and IFN-λ3 treatments were failure to obviously inhibit the viral infection and early replication in vitro. Furthermore, the blueprint of virus-host interaction was plotted by RNA-seq and RT-qPCR, showing systemic activations of inflammatory, apoptotic, and antiviral pathways in response to GETV infection, whereas indicating viral hijacking and inhibition of the host innate immunity such as IFN-Ⅰ/III responses. Last and most importantly, activation of JAK-STAT signaling pathway, coupled with complement and coagulation cascades, may be the primary driver for IFN-γ-mediated inhibition of GETV replication. These findings revealed that GETV possessed the capability of viral immune escape, and indicated that IFN-γ aided for prevention and control of GETV, implied the potential molecular mechanism of suppression on GETV by IFN-γ, all warrant emphasis or further clarification.